16a+17b+2c+2c-4b-3a=

Simple and best practice solution for 16a+17b+2c+2c-4b-3a= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 16a+17b+2c+2c-4b-3a= equation:


Simplifying
16a + 17b + 2c + 2c + -4b + -3a = 0

Reorder the terms:
16a + -3a + 17b + -4b + 2c + 2c = 0

Combine like terms: 16a + -3a = 13a
13a + 17b + -4b + 2c + 2c = 0

Combine like terms: 17b + -4b = 13b
13a + 13b + 2c + 2c = 0

Combine like terms: 2c + 2c = 4c
13a + 13b + 4c = 0

Solving
13a + 13b + 4c = 0

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-13b' to each side of the equation.
13a + 13b + -13b + 4c = 0 + -13b

Combine like terms: 13b + -13b = 0
13a + 0 + 4c = 0 + -13b
13a + 4c = 0 + -13b
Remove the zero:
13a + 4c = -13b

Add '-4c' to each side of the equation.
13a + 4c + -4c = -13b + -4c

Combine like terms: 4c + -4c = 0
13a + 0 = -13b + -4c
13a = -13b + -4c

Divide each side by '13'.
a = -1b + -0.3076923077c

Simplifying
a = -1b + -0.3076923077c

See similar equations:

| 2i+7=5i-2 | | 11p+19q+p-3q-6p= | | 3(2x-5)=27 | | x+(x+6)+12=66 | | 71-2x=34x+23 | | 14m+6n-4m+7n= | | (x+6)+12=66 | | 14-7x=110-35x | | 6a+1=2a+25 | | X^2-71*x+72=0 | | 2x+3=19+x | | -26-7x=110-35x | | -3x^2=-12 | | 180-7x=20x+21 | | 9t-3=8t-18 | | 7y+3=12y+8 | | -155-7x=10x+15 | | -155-7x=10x+25 | | 18+4y=18 | | 8x^2+3x+10=0 | | 6n-7=3n+2 | | 5x-18=22 | | 3x+7x=8 | | 3n+6=n+10 | | 7x^2-6x-111=0 | | 4.4x+3.8=13.2 | | 4x+34=12x-38 | | 4*0.5-3y=11 | | 2x+9=51-8x | | 10x-29=71 | | 76-4x=7+21 | | 4x-3*-3=7 |

Equations solver categories